2020
DOI: 10.3390/molecules25215042
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-Mediated Synthesis of Silver Nanoparticles Using Terminalia chebula Fruit Extract and Evaluation of Its Cytotoxic and Antimicrobial Potential

Abstract: The increasing interest in developing potent non-toxic drugs in medicine is widening the opportunities for studying the usage of nanostructures in the treatment of various diseases. The present work reports a method for a facile and an eco-friendly synthesis of silver nanoparticles (AgNPs) using Terminalia chebula fruit extract (TCE). The obtained AgNPs was characterized by using different spectroscopic and microscopic techniques. The analysis of the results revealed that the as-obtained AgNPs have spherical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
4
12
1
Order By: Relevance
“…Other groups reported recently similar results with plant biosynthesized AgNP [ 13 , 25 , 26 , 27 , 28 , 29 ]. Gram-positive and Gram-negative pathogens are susceptible to reported AgNP biohybrids [ 13 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…Other groups reported recently similar results with plant biosynthesized AgNP [ 13 , 25 , 26 , 27 , 28 , 29 ]. Gram-positive and Gram-negative pathogens are susceptible to reported AgNP biohybrids [ 13 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Resultssupporting
confidence: 67%
“…Other groups reported recently similar results with plant biosynthesized AgNP [ 13 , 25 , 26 , 27 , 28 , 29 ]. Gram-positive and Gram-negative pathogens are susceptible to reported AgNP biohybrids [ 13 , 25 , 26 , 27 , 28 , 29 ]. DD studies showed similar zones of inhibition for S. aureus (13/14 mm), E. coli (12 mm), and P. aeruginosa (9 mm) [ 13 ].…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations